[OA130] Adaptation of external beam radiotherapy through daily cone beam CT monitoring for cervical cancer patients. (August 2018) - Assenholt, Marianne Sanggaard; Vestergaard, Anne; Kjærsgaard, Eva Bruun; Schouboe, Annette; Nyvang, Lars; Lindegaard, Jacob C.; Tanderup, Kari; Fokdal, Lars U.; Kibsgaard Jensen, Nina Boje
Abstract : Purpose: To evaluate an image-guided and adaptive EBRT workflow in locally advanced cervical cancer (LACC) patients treated according to EMBRACE II guidelines in terms of individualized ITV margins and new criteria for dose coverage. Interfractional target-(cervix/uterus) and organ filling was monitored on a daily basis and investigated along with the impact of patient feedback on organ fillings. Methods: Patients treated with definitive radiochemotherapy were included. Pretreatment MRI- and (PET)-CT scans with full and empty bladders were performed and a bladder-filling protocol applied. Contouring was according to EMBRACE II guidelines with individualized ITV margin and 5 mm PTV margin. VMAT plans were used to deliver 45Gy/25 fractions with daily onboard cone beam CT (CBCT) scans. Trained RTTs monitored the interfractional target motion and organ fillings, and provided patients with daily feedback on organ-filling. A clinical workflow including thresholds for re-planning if target was not inside PTV was designed and followed. CBCTs were retrospectively reviewed, and the accuracy of the RTT scorings analyzed. Minimum doses to CTV-T HR(aim 42, 75 Gy) and CTV-T LR(aim 40 Gy) were retrospectively estimated for replanned patients. Results: Twenty-three patients were evaluated. RTT scoring of target coverage was correct in 90% of the CBCTs (505/563), incorrect in <1%, and in 7% of the CBCTs the RTTs could not score primary due to compromised image quality. Seven patients were re-planned based on lack of target coverage. Minimum dose assessment indicated that delivered dose had been within aims without re-planning for 3/7 patients. One patient had considerable benefit of re-planning with an improvement of 12.7 Gy to CTV-T LR vagina. Re-planning improved CTV-T LR uterus by 1.2–1.8 Gy in 4 patients, and 3 patients gained less than 1 Gy. Lack of coverage was more often caused by rectal/bowel than bladder-filling. Conclusions: The study proposes a practical adaptive approach for EBRT in LACC patients with daily IGRT monitoring supporting the EMBRACE II guidelines. The strategy allowed safe treatment with relatively tight ITV margins. In patients with unpredictable interfractional target- and organ motion, the compromised coverage benefitted from re-planning. The approach has limited workload and can be performed with high accuracy by RTTs.